2014
DOI: 10.1097/mpg.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Spanish National Registry of Celiac Disease

Abstract: In Spain, the most frequent clinical presentation of CD is the classical form, mainly diagnosed during the first 2 years of life. The observed incidence of CD in Spanish children is much higher than the present CD incidence rates observed in other European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…Similar low frequencies of DQ8 have been reported in children with CD from other Spanish regions (22)(23)(24)(25). In addition, the frequencies observed in our Spanish controls differ from those reported in the North of Europe and are slightly lower for DQ2.5.…”
Section: Discussionsupporting
confidence: 69%
“…Similar low frequencies of DQ8 have been reported in children with CD from other Spanish regions (22)(23)(24)(25). In addition, the frequencies observed in our Spanish controls differ from those reported in the North of Europe and are slightly lower for DQ2.5.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study a peak value at 9.9 years was observed (data not shown), one of the highest reported internationally. On the contrary, other studies have reported that the age at diagnosis has not shifted upwards, instead remaining at the same level as in the pre-epidemic and epidemic periods in Sweden [ 23 , 24 ]. Both genetic background and different diet practice among those populations could contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 89%
“…As age increased, the gap in cumulative incidence between the epidemic cohort and the pre-epidemic and post-epidemic cohorts became wider. The cumulative incidence in a Spanish cohort of patients with CD and mean age at diagnosis of 2.3 years, recorded in their national register between 2006−2007 was almost 7 cases/1000 births [ 24 ]. Our results, 13.8 cases/1000 births at 18 years-of-age, are presumably the highest cumulative incidence rates ever reported [ 24 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] Most studies of the epidemiology of CD were conducted in Europe, with incidence estimated between 2 and 54 cases per 100,000 patient-years (PY). [710]…”
Section: Introductionmentioning
confidence: 99%